Identification of Novel KMT2B Variants in Chinese Dystonia Patients via Whole-Exome Sequencing - Ma, Jun; Wang, Lin; Yang, Yingmai; Li, Shanglin; Wan, Xinhua (Frontiers in Neurology, 2019)
Background: Dystonia is a movement disorder with high clinical and genetic heterogeneity. Recently mutations in lysine-specific histone methyltransferase 2B (KMT2B) gene have been reported to be associated with early-onset progressive dystonia. Methods: We performed whole-exome sequencings in a cohort of early-onset dystonia patients from China. Bioinformatics analysis and cosegregation testings were conducted to select candidate causal variants. The effects of identified variants were classified according to the American College of Medical Genetics and Genomics (ACMG) standards and guidelines. Results: Three novel KMT2B variants were identified, including p.Q1359* in patient 1, p.R1487AfsTer7 in patient 2, and p.R152W in patient 3. Among these variants, the nonsense variant p.Q1359* and the frameshift variant p.R1487AfsTer7 showed high pathogenicity and were rated as pathogenic according to the ACMG guideline. Regarding the phenotypes of these two patients with pathogenic variants, patient 2 showed the similar presentation as reported whereas patient 1 seemly harbored the atypical presentations, including later onset age, atypical sites of onset and milder degree of dystonia. Conclusions: We further report three dystonia patients with novel variants in KMT2B and expand the spectrums of genotype and phenotype of KMT2B.